Internship Reports and Monograph entitled "Myocarditis and its Importance in the Context of COVID-19 Infection and following mRNA Vaccination" - Gil, Maria Inês Pereira (2022)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia